A multifunctional DNA nanostructure based on multicolor FRET for nuclease activity assay. Issue 18 (11th August 2020) - Hu, Juan; Li, Wen-can; Qiu, Jian-Ge; Jiang, BingHua; Zhang, Chun-yang
Abstract : We develop a four-color fluorescent probe for ratiometric detection of multiple nucleases based on multistep fluorescence resonance energy transfer. Abstract : Nucleases play a crucial role in DNA replication, recombination and repair which are associated with cancers. Herein, we develop a four-color fluorescent probe for ratiometric detection of multiple nucleases. This four-color fluorescent probe consists of four fluorescent dyes connected by a DNA tetrahedral nanostructure with the involvement of multistep fluorescence resonance energy transfer (FRET). Based on the principle of self-assembly, the four-color fluorescent probe is constructed by integrating one acceptor with three spatially and spectrally distinct acceptors. A DNA tetrahedral nanostructure functions as a scaffold to link the acceptor dyes ( i.e., diethylaminocoumarin (DEA), carboxyfluorescein (FAM), Texas Red, and Cy5). The fluorescence emissions of DEA, FAM, Texas Red and Cy5 can be observed through efficient multi-step energy transfer. This four-color fluorescent probe enables single excitation/four emissions, and it can be used for ratiometric detection of nucleases ( i.e., XhoI, HindIII and KpnI) and the screening of nuclease inhibitors. Importantly, this four-color fluorescent probe can be further applied to discriminate multiple biomolecule targets by simply integrating the recognition sites of various biomolecules into the DNA tetrahedral nanostructure.